Bioaccumulation of heavy metals in different organs of Labeo rohita, Pangasius hypophthalmus, and Katsuwonus pelamis from Visakhapatnam, India. (August 2020) - Pragnya, M.; Dinesh Kumar, S.; Solomon Raju, A.J.; Murthy, L.N.
Abstract: The bioaccumulation of heavy metals (Zn, Pb, Cd, Co, Cu, and Fe) in fish tissues was determined using Atomic Absorption Spectrometer (spectra 220) and Mercury (Hg) content was estimated by using a mercury analyzer. Various organs (eye, gill, gut, gonad, liver, skin, and muscle) of three fish species, i.e., Labeo rohita, Pangasius hypophthalmus and Katsuwonus pelamis, from Visakhapatnam were analyzed. Young and aged fish were chosen based on their length: LR-32, LR-49 (Rohu); PH-33, PH-56 ( Pangasius ); and KP-18, KP-52 (Skipjack). In both the small and big size of L. rohita and P. hypophthalmus, the metal concentration was in the order Fe > Zn > Cu whereas Pb, Hg, and Co were below detectable limit (BDL). Concentrations in K. pelamis was Fe > Zn > Cu > Cd and Pb, Hg, and Co were BDL. In conclusion, the metal concentrations in the examined fish species available in Visakhapatnam fall below the maximum permissible limit (MPL) for human consumption recommended by FAO, WHO, MAFF, and EC. Highlights: Rapid growth in Visakhapatnam is leading to water pollution. Fish are important bio indicators of pollution. Katsuwonus, Labeo and Pangasius represent different hydrospheres. Heavy metals in various fish organs indicate good quality in fresh water. Marine pollution is indicated by analysis in skipjack tuna.